The Law on the Tripple Talaq at Once in the View of Yusuf Al Qaradawi's in Contemporary Context: Analysis of Sadd Al-Żarī'ah Theory - Yuhasnibar, Yuhasnibar; Wati, Risna (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Triple talaq (Third Divorce) at once is a prominent topic in Islamic jurisprudence that continues to be of great interest to modern academics, including Yusuf Al-Qaradawi. Yusuf Al-Qaradawi holds a divergent perspective from the majority of ulama who regard the law on maximum talaq at once as equivalent to triple talaq (the one mentioned three times). This research seeks to analyze Yusuf al-Qaradawi's perspectives on triple talaq at once by employing the sadd al-żarī'ahtheory. This study employs a normative legal approach, utilizing the sadd al-żarī'ah theory for descriptive and analytical analysis. According to Yusuf al-Qardhawi, maximum talaq at once is illegal due to its non-compliance with the commandments of Islamic law. The process of divorce should follow several steps, including the initial divorce, followed by the iddah period, and then the possibility of reconciliation. The second or third divorce procedure can be pursued if reconciliation is not achieved. The argument presented relies on the historical account of Imam Muslim from Ibn Abbas, which elucidates that the occurrence of maximum talaq at once throughout the era of the Prophet, Abu Bakr, and the first two years of Umar's caliphate was seen as a single talaq. Ibn Wahhab's historical account of Al-Nasa'i documents the incident where the Messenger of Allah declined to listen to the news of a maximum divorce being pronounced simultaneously. The historical account of Abu Dawud, as related by Nafi', documented the divorce of Rukanah from his wife, which eventually reached the Messenger of Allah. According to Yusuf Al-Qaradawi, the immediate restriction of the maximum talaq at once is an attempt to conceal the harm caused. The fundamental principle of sadd al-żarī'ah's theory posits that every action that is forbidden by the Qur'an and hadith is intended to hinder the occurrence of harm or wrongdoing.